2017
DOI: 10.25268/bimc.invemar.2017.46.1.719
|View full text |Cite
|
Sign up to set email alerts
|

Detección De Cambios De La Línea Costera Al Norte Del Distrito De Buenaventura Mediante El Uso De Sensores Remotos

Abstract: This study focuses on detecting the magnitude of shoreline changes of the northern District ofBuenaventura, in the Colombian Pacific, over a 30-year period, on a coast where the geomorphologyincludes beaches, cliffs, estuaries, deltas and salt marshes. Satellite imagery (Landsat MSS, ETM + andOLI TIRS) were used to detect historical positions of the shoreline in order to identify the processes ofchange, in terms of erosion and accretion, from 1986 to 2015. Statistical analysis of changes was carriedout to esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…There was a general trend in coastline accretion according to the average EPR of 2.8 m/year, with a total accretion of 48%. However, the Cifuentes [31] study from 1986 to 2015 showed that, on average, a change rate of −0.2 m/year occurred, reflecting an erosion trend with maximum EPR values of 26.9 m/year of accretion and −21 m/year of coastal erosion. The marked differences in the values of the previous study with those of this study may be explained from the higher temporal coverage used in this work, mainly in the La Concepción beach area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There was a general trend in coastline accretion according to the average EPR of 2.8 m/year, with a total accretion of 48%. However, the Cifuentes [31] study from 1986 to 2015 showed that, on average, a change rate of −0.2 m/year occurred, reflecting an erosion trend with maximum EPR values of 26.9 m/year of accretion and −21 m/year of coastal erosion. The marked differences in the values of the previous study with those of this study may be explained from the higher temporal coverage used in this work, mainly in the La Concepción beach area.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Furlan et al [30] developed a multidimensional CVI to evaluate vulnerability to flood scenarios along the Italian coast considering multiple indicators. Although there are studies that evaluate the general vulnerability of the coasts of Buenaventura [13,21,22,31,32], these have focused mainly on geomorphological and physical dimensions. Numerous studies have been conducted around the world to examine different aspects of coastal vulnerability with a geospatial approach using the CVI and COVI (Table 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Colombia, different studies on coastal erosion have been undertaken, starting with the descriptive analyses carried out by Posada and Henao Pineda [6] and Posada et al [7,8], which generated the first coastal erosion maps of the country from observations of coastal geomorphological features. These studies were later complemented with quantitative analyses through the calculation of changes in coastlines and the use of GIS tools [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, satellite imagery and shoreline detection have been widely developed and used for a long time, and range from the manual digitization of the coastline to proven automated processes [13][14][15][16]. In the same way, the quantitative evaluation of changes that occur on coasts using tools such as DSAS [17][18][19] has been very popular, and there are countless publications on this [9,11,18,20,21]. The use of this metric requires multiple corrections and rules [22] in order to obtain values close to reality, but before defining which method and tools to use, the objective must be defined; that is, one must define the purpose of this metric, and from that, choose appropriate elements.…”
Section: Introductionmentioning
confidence: 99%